(untitled) (International Journal of Environmental Sciences, 2025)
Extensive and arbitrary use of food additives in restaurant dishes and food colors production in industries have caused impending hazards to aquatic organisms. Fishes occupying higher positions in trophic level of the aquatic food chain suffers the most due to the industrial discharge and hotel run off. Reproductive system is one of the most important systems which gets affected to a great extent and in turn affects the reproductive processes and fecundity of animals. Present investigation aims with potential effects of Allura red (AR), (E129) (FD&C Red Dye #40 or Red 40) is a dark-red, water-soluble, azo dye . It is used as food dye for the replacement of amaranth.. Allura red is originally derived from petroleum. It is added into soft drinks, children’s medications, and cotton candy. This is the most commonly used dye in the United States for beverages, meats, cheeses, salmon, over-the-counter (OTC) medications, and liquid suspensions etc. On the histological profile of ovary of a fresh water food fish Channa punctata (Bloch) after 15, 30 and 45 days of exposure periods. Notable histopathological findings include deshaped ovum, ruptured ovarian epithelium, stromal hemorrhage, and vacuolization in the ovaries. The extent of ovarian damage was exposure dependent under the impact of individual toxicants. The results obtained will be helpful to understand the effect of Allura red on the ovary of fishes. The findings are quite suggestive of reproductive impairments leading to delayed ovarian maturity and adversely affecting process of ovulation and thus, fish production.